2022
DOI: 10.1002/advs.202203681
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Chromium Multioxide Hole‐Selective Heterojunction for High‐Performance Perovskite Solar Cells

Abstract: Perovskite solar cells (PSCs) suffer from significant nonradiative recombination at perovskite/charge transport layer heterojunction, seriously limiting their power conversion efficiencies. Herein, solution-processed chromium multioxide (CrO x ) is judiciously selected to construct a MAPbI 3 /CrO x /Spiro-OMeTAD hole-selective heterojunction. It is demonstrated that the inserted CrO x not only effectively reduces defect sites via redox shuttle at perovskite contact, but also decreases valence band maximum (VBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…As shown in Figure 4c, compared with the perovskite thin film prepared without the PCBM charge-transport layer, the DADA-treated perovskite thin film has a PL intensity that is almost twice that of the former. The enhanced PL intensity (Figure 4c) reveals that DADA helps to suppress nonradiative recombination by eliminating defect sites on the perovskite thin-film surface, 42 which is consistent with the longer carrier lifetime for the DADA-treated perovskite thin film compared to the control perovskite thin film, according to the TRPL spectra in Figure 4d. The PL attenuation curve was fitted using the following double exponential function (eq 1), 44 and the fitted results are listed in Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 4c, compared with the perovskite thin film prepared without the PCBM charge-transport layer, the DADA-treated perovskite thin film has a PL intensity that is almost twice that of the former. The enhanced PL intensity (Figure 4c) reveals that DADA helps to suppress nonradiative recombination by eliminating defect sites on the perovskite thin-film surface, 42 which is consistent with the longer carrier lifetime for the DADA-treated perovskite thin film compared to the control perovskite thin film, according to the TRPL spectra in Figure 4d. The PL attenuation curve was fitted using the following double exponential function (eq 1), 44 and the fitted results are listed in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…The UV−vis absorption spectra of the MAPbI 3 and MAPbI 3 /DADA thin films are shown in Figure 3f. Owing to both the improved perovskite thin-film crystallization and fewer interfacial defects, 42 the optical absorbance of the MAPbI 3 /DADA thin film was slightly enhanced. The Tauc diagram (Figure S7) revealed that DADA did not change the bandgap of the film (1.58 eV).…”
Section: Resultsmentioning
confidence: 99%
“…, [37][38] the calculated hole transfer efficiency (η t ) between the perovskite and PTAA:F4TCNQ largely increases from 53.04% to 91.4% at the PTAA:F4TCNQ/DA/perovskite:DA heterojunction.…”
Section: Resultsmentioning
confidence: 99%
“…[ 35–36 ] Moreover, the photoluminescence quantum yields (PLQYs) for the perovskite, DA/perovskite, and DA/perovskite:DA are 1.15%, 3.88%, and 6.98%, respectively, and the PLQYs of the corresponding films with PTAA:F4TCNQ are 0.54%, 0.40% and 0.60%, respectively. According to the equation: ηt=(1PLQYPVK/HTLPLQYPVK)${\eta _t} = \left( {1 - \frac{{PLQ{Y_{PVK/HTL}}}}{{PLQ{Y_{PVK}}}}} \right)$, [ 37–38 ] the calculated hole transfer efficiency (η t ) between the perovskite and PTAA:F4TCNQ largely increases from 53.04% to 91.4% at the PTAA:F4TCNQ/DA/perovskite:DA heterojunction.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, almost all efforts focus on improving the power conversion efficiency (PCE) and the stability of mixedcation PSCs, e.g. additive engineering [23,24] , crystallization engineering [25,26] , component engineering [27] , interface engineering [28,29] , film-making technique [30,31] , passivation [32−34] , tandem cells [35−38] , large-area fabrication [39−41] , and flexible devices [42,43] . The precursor ageing issue does not receive enough attention.…”
mentioning
confidence: 99%